Variance and potential niche separation of microbial communities in subseafloor sediments off Shimokita Peninsula, Japan. (10th December 2015) - Nunoura, Takuro; Takaki, Yoshihiro; Shimamura, Shigeru; Kakuta, Jungo; Kazama, Hiromi; Hirai, Miho; Masui, Noriaki; Tomaru, Hitoshi; Morono, Yuki; Imachi, Hiroyuki; Inagaki, Fumio; Takai, Ken
Summary: Subseafloor pelagic sediments with high concentrations of organic matter form habitats for diverse microorganisms. Here, we determined depth profiles of genes for SSU rRNA, mcrA, dsrA and amoA from just beneath the seafloor to 363.3 m below the seafloor (mbsf) using core samples obtained from the forearc basin off the Shimokita Peninsula. The molecular profiles were combined with data on lithostratigraphy, depositional age, sedimentation rate and pore‐water chemistry. The SSU rRNA gene tag structure and diversity changed at around the sulfate‐methane transition zone (SMTZ), whereas the profiles varied further with depth below the SMTZ, probably in connection with the variation in pore‐water chemistry. The depth profiles of diversity and abundance of dsrA, a key gene for sulfate reduction, suggested the possible niche separations of sulfate‐reducing populations, even below the SMTZ. The diversity and abundance patterns of mcrA, a key gene for methanogenesis/anaerobic methanotrophy, suggested a stratified distribution and separation of anaerobic methanotrophy and hydrogenotrophic or methylotrophic methanogensis below the SMTZ. This study provides novel insights into the relationships between the composition and function of microbial communities and the chemical environment in the nutrient‐rich continental margin subseafloor sediments, which may result in niche separation and variability in subseafloor microbial populations.